2005
DOI: 10.1111/j.1539-6924.2005.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Improbability of Igneous Intrusion Promoting a Critical Event in Spent Nuclear Fuel Disposed in Unsaturated Tuff

Abstract: In their regulations, the U.S. Environmental Protection Agency and the U.S. Nuclear Regulatory Commission permit the omission of features, events, or processes with probabilities of <10(-4) in 10(4) yr (e.g., a constant frequency of <10(-8) per yr) in assessments of the performance of radioactive waste disposal systems. Igneous intrusion (or "volcanism") of a geologic repository at Yucca Mountain for radioactive waste is one disruptive event that has a probability with a range of uncertainty that straddles thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…EPA issued its revised and long awaited offsite health standards under the NWPA in June 2001, which set a limit to the release of radioactivity to the environment at 15 millirems per year for 10,000 years after disposal, a time frame without precedent (Cameron and Solomon 1990). The standard had three components: an individual human protection standard, a human intrusion standard, and multiple groundwater protection standards (Rechard and Tierney 2005). These regulations are also applicable at WIPP, where EPA must review DOE's recertification application every five years based on the regulations found in 40 CFR 194 until the facility closes (WIPP was last recertified in March 2006).…”
Section: Principles Norms Rules and Proceduresmentioning
confidence: 99%
“…EPA issued its revised and long awaited offsite health standards under the NWPA in June 2001, which set a limit to the release of radioactivity to the environment at 15 millirems per year for 10,000 years after disposal, a time frame without precedent (Cameron and Solomon 1990). The standard had three components: an individual human protection standard, a human intrusion standard, and multiple groundwater protection standards (Rechard and Tierney 2005). These regulations are also applicable at WIPP, where EPA must review DOE's recertification application every five years based on the regulations found in 40 CFR 194 until the facility closes (WIPP was last recertified in March 2006).…”
Section: Principles Norms Rules and Proceduresmentioning
confidence: 99%